Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41467-021-21140-4
|View full text |Cite
|
Sign up to set email alerts
|

The tight Second Law inequality for coherent quantum systems and finite-size heat baths

Abstract: In classical thermodynamics, the optimal work is given by the free energy difference, what according to the result of Skrzypczyk et al. can be generalized for individual quantum systems. The saturation of this bound, however, requires an infinite bath and ideal energy storage that is able to extract work from coherences. Here we present the tight Second Law inequality, defined in terms of the ergotropy (rather than free energy), that incorporates both of those important microscopic effects – the locked energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(49 citation statements)
references
References 50 publications
0
48
0
Order By: Relevance
“…For the sake of simplicity, we further assume that the eigenenergies are ordered in ascending magnitude, . As an alternative expression, the quantum ergotropy can be expressed as the difference of relative entropies [ 14 , 48 ] (see Appendix B for the proof) …”
Section: Quantum Ergotropymentioning
confidence: 99%
“…For the sake of simplicity, we further assume that the eigenenergies are ordered in ascending magnitude, . As an alternative expression, the quantum ergotropy can be expressed as the difference of relative entropies [ 14 , 48 ] (see Appendix B for the proof) …”
Section: Quantum Ergotropymentioning
confidence: 99%
“…In order to take full advantage of these techniques it is crucial to understand how thermodynamic laws translate into the non-equilibrium domain, where fluctuations of thermodynamic quantities begin to play a significant role and averaged quantities are no longer enough to characterize their thermodynamic behaviour. This motivates extending thermodynamic framework to systems driven out of equilibrium, a setting which has been extensively studied in the recent literature [7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…We stress that this is unavoidable if one wants to incorporate interference effects since the processing of coherences of the system strongly depends on coherences of the work reservoir. In particular, treating the energy-storage device explicitly leads to the so-called work-locking [18,19] (i.e., an inability of work extraction from coherences), which non-autonomous frameworks cannot even capture.…”
Section: Introductionmentioning
confidence: 99%
“…[24] where are discussed corrections if translational invariance is violated). Moreover, it has also been shown that the optimal work extracted by the quantum weight is limited by the ergotropy [19,25], which, with the notion of passivity, is another building block of quantum thermodynamics (see, e.g., [26,27]). Hence, taking the weight as a proper model for fluctuation theorems allows us to analyze the quantum coherences, from a thermodynamic perspective, within a fully quantum setup.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation